Bis(2-amino-6-methyl-pyrimidin-1-ium-4-olate-κN,O)bis-(nitrato-κO,O')cadmium(II) - Kaabi, Kamel (2010)
In the title compound, [Cd(NO(3))(2)(C(5)H(7)N(3)O)(2)], the Cd(II) atom is eight-coordinated by two amine N atoms and two O atoms from two zwitterionic, biodentate 2-amino-6-methyl-pyrimidin-1-ium-4-olate ligands and by four O atoms from two nitrate groups. Intra-molecular N-H⋯O hydrogen bonds occur. The crystal packing is stabilized by inter-molecular N-H⋯O and C-H⋯O hydrogen bonds, two of which are bifurcated, between the nitrate anions and the organic groups.